Contribuição à taxonomia de Marlierea (Myrciinae; Myrtaceae) no Brasil - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2013)
This paper presents a taxonomic circumscription of Marlierea and three new records of occurrence for the genus in the Brazilian Amazon, two in Brazil, three for the State of Pará and one for the State of Amazonas. Comments on the morphology and affinity of taxa are provided to facilitate recognition of each species, as well as their geographical distribution data and typical environments occurrence of these species in the Amazon region. Recommendations for updating the list of Brazilian Myrtaceae species are presented.
Contribution to the taxonomy of Marlierea (Myrciinae; Myrtaceae) in Brazil
Keywords: Amazônia; circunscrição taxonômica; fitofisionomia; morfologia; novos registros; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA